Digital Economy and Digital Labour Terminology : Making Sense of the “Gig Economy”, “Online Labour”, “Crowd Work”, “Microwork”, “Platform Labour”, Etc. /: Making Sense of the “Gig Economy”, “Online Labour”, “Crowd Work”, “Microwork”, “Platform Labour”, Etc. (2017) - Heeks, Richard, 1960-
No abstract available